Reconstruction of Business Competition Law Policy Against Well-Meaning Perpetrators in Cartel Cases: A Substantive Justice And Proportionality Approach - Sutrisno, Sutrisno; Wibowo, Basuki Rekso; Hasibuan, Fauzie Yusuf (Sahabat Publikasi, 2025)
Law enforcement against cartel practices in Indonesia continues to face challenges in upholding substantive justice. The prevailing per se illegal approach tends to treat all business actors involved in a cartel structure equally, without considering their intent, position, or degree of involvement. This results in disproportionate sanctions being imposed on business actors who lack malicious intent or who are merely performing administrative functions. This study aims to analyze the form of legal protection for good-faith business actors involved in cartel cases and to formulate the direction of a more just and proportional competition law policy. The research employs a normative juridical approach, using literature review, analysis of statutory regulations, decisions from the Indonesian Business Competition Supervisory Commission (KPPU), and comparative studies with other jurisdictions. The findings reveal the necessity of distinguishing between principal and passive actors, applying a tiered liability system, and providing legal defenses based on intent and actual contribution. This reconstruction is expected to enhance the legitimacy of competition law enforcement and foster a fair and balanced business climate.